2014
DOI: 10.1038/nrneurol.2014.196
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms and treatment of ischaemic stroke—insights from genetic associations

Abstract: | The precise pathophysiology of ischaemic stroke is unclear, and a greater understanding of the different mechanisms that underlie large-artery, cardioembolic and lacunar ischaemic stroke subtypes would enable the development of more-effective, subtype-specific therapies. Genome-wide association studies (GWASs) are identifying novel genetic variants that associate with the risk of stroke. These associations provide insight into the pathophysiological mechanisms, and present opportunities for novel therapeutic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 80 publications
1
41
0
1
Order By: Relevance
“…About 80% of all strokes are ischemic, 1 but this term describes a syndrome caused by a number of different pathologies, which may have different treatments. 2 The major etiologies of ischemic stroke are large artery atherosclerosis (large artery stroke), small vessel atherosclerosis (small vessel stroke), and cardioembolism (cardioembolic stroke). Recent data from genomewide association studies (GWAS) have shown that these subtypes have distinctive risk factor profiles and, by implication, diverse pathophysiologic bases.…”
Section: Discussionmentioning
confidence: 99%
“…About 80% of all strokes are ischemic, 1 but this term describes a syndrome caused by a number of different pathologies, which may have different treatments. 2 The major etiologies of ischemic stroke are large artery atherosclerosis (large artery stroke), small vessel atherosclerosis (small vessel stroke), and cardioembolism (cardioembolic stroke). Recent data from genomewide association studies (GWAS) have shown that these subtypes have distinctive risk factor profiles and, by implication, diverse pathophysiologic bases.…”
Section: Discussionmentioning
confidence: 99%
“…This approach has identified more than a thousand novel associations with risk of complex diseases including stroke,53 as well as pharmacogenomic effects on the risk of bleeding in patients receiving anticoagulants or antiplatelet agents 54. Screening for these genetic variants in patients with acute stroke is currently too time consuming to be practical prethrombolysis, though specific point-of-care genetic testing may be possible in the future.…”
Section: General Molecular Mechanisms Of Thrombolysismentioning
confidence: 99%
“…Meta-analysis by the METASTROKE collaboration and review of Genome Wide Association Studies (GWAS) for ischaemic stroke found most genetic variant associations were specific to a subtype, suggesting different subtypes have different risk factor profiles and pathophysiological mechanisms (Markus and Bevan, 2014;Traylor et al, 2012).…”
mentioning
confidence: 99%